Synthesis of nanohydroxypatite-silica hybrid By in-situ sol-gel for fabrication of glass lonomer cement (GIC) dental nanocomposites - Rahman, Ismail Ab. (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2015)
Glass ionomer cements (GICs) have been widely used as restorative dental materials due to the biocompatibility property that able to form direct bonding to the tooth structure and the release of fluoride ions that protect against dental caries and able to regenerate hard tissues including bones and tooth structure. Among the disadvantages, GICs are chemically soluble in saliva water environment that need a protective layer of methacrylate based gloss, the setting reaction affected by water, abrasive, weak in mechanical properties such as strength and hardness. Thus, it is required to develop new composition and the studies on the improvement of the mentioned aspects in order to find a better product for future restorative dental material. Modification of commercial GICs with hydroxyapatite (HA) stainless steel, zirconia, glass, HNzirconia, HNglass have been reported in literatures to improve mechanical properties. However, the improvement on mechanical properties was not significant. In all cases, they used commercial powders with particle size in micro range. In addition, a fundamental studies on the effect of powder morphologies and the interaction between additive and GIC that affect mechanical and chemical and biological properties were not elaborated. In our knowledge, the work on the addition of HNsilica nanoparticle is not yet reported in literature. This work is aimed to produce a new composition of GIC by incorporation of nano HAsilica hybrid to obtain nanocomposites with superior properties. The HA-silica hybrid is derived from in-situ sol-gel process that has been developed in our laboratory. Therefore, incorporation of HA-silica inside the GIC has improved the hardness due to the better interaction between HA-silica-GIC and homogeneous distribution of additives